VIENNESE SECESSION AND THE BEGINNING OF EUROPEAN ART DECO - A. S. Dobrydneva (Концепт: философия, религия, культура, 2019)
The article is dedicated to the art of the Viennese Secession style of the late period. It is argued that the association Secession and its handicraft venture - Vienna Workshop is a turning point in the formation of the new decorative art (art deco), while in its program it partly remains in the positions of the art nouveau style. The paper considers primarily the creativity of the founders of workshops - J. Hoffman, K. Moser and G. Klimt. As the works synthesizing different types of art, there are two fully realized projects - a sanatorium Purkersdorf and the Palais Stoclet. Both could be taken into account as a Gesamtkunstwerk, works of art that make use of all art forms.Art Deco highlighted the categories of “quality of life” and “comfort”, but it must be remembered that this trend also appeared in late modernism. So, “artists who in the 1890s under the guise of Secession, got involved in an active search for a new truth - the truth of instincts, now turned away from their alarming discoveries and set about solving a more modest and profitable task: to decorate the everyday life and home life of the Vienna elite. ” According to Hoffman, artists must now solve exclusively creative tasks, and not engage in politics. This point of view is different from the lifebuilding pathos with which the early manifestos of modernity were full. If at most exhibitions since 1898 the slogan “Art for the time. Freedom for art” triumphed, then the catalog of 1908 began with the epigraph “Art never expresses anything but itself.”